Screening of Antifungal Activity of Selected Species against Candida Species - Karawita, K.V.D.S.H.; Fernando, K.M.E.P.; Wijendra, W.A.S. (University of Sri Jayewardenepura, Nugegoda, 2015)
The fungus Candida is an opportunistic pathogen which causes superficial and systemic candidasis, and associated with significant mortality and morbidity in health care settings. Development of resistance towards antifungal drugs which are currently used to treat Candida infections and associated high risk of side effects of some drugs have been reported. It is imperative to explore suitable alternative treatments for Candida infections. The objective of this study was to evaluate antifungal activity of selected spices against Candida species. Aqueous and methanol extracts of five different medicinal plants: Garlic (Allium sativum L), onion (Allium cepa), ginger (Zingiber officinale), lime (Citrus urantifolia) and nutmeg (Myristica fragrans) which are consumed as spices were screened for antifungal activity against four Candida species; C. albicans, C. tropicalis, C. glabrata and C. parapsilosis. Well diffusion method and bioassay method on percentage inhibition of mycelial growth were carried out to determine the inhibitory activity of the extracts. Ketoconazole was used as positive control while water and methanol were used as negative controls. Aqueous and methanol extracts of garlic, methanol extracts of onion and nutmeg exhibited antifungal activity against tested Candida species giving remarkable inhibition zones. Methanol extract of garlic showed higher antifungal activity (inhibition zone range from 38.00 to 45.66 mm) than that of positive control (inhibition zone range from 20.33 to 32.33 mm) against all Candida species tested. All the tested Candida species exhibited 100% growth inhibition for methanol extracts of nutmeg and garlic. Relatively low antifungal effect was observed for methanol extract of onion showing low percentage of mycelial growth inhibition for C. glabrata (24.66%) and C. tropicalis (28.00%). Aqueous extracts of ginger and lime did not show antifungal activity. This study reveals that aqueous and methanol extracts of garlic and methanol extracts of nutmeg and onion exhibit antifungal activity against tested Candida species. Fungicidal properties of the extracts indicate the potential of selected spices as a source of alternative drug for Candida infections. Further studies are needed to identify active compounds responsible for the antifungal activity of these spices.
Keywords: antifungal activity; fungus